Ferric (III) Chloride-Catalyzed Synthesis of 3, 4-Dihydropyrimidine-2(1H) Ones / Thiones for Biginelli Reaction and Characterization of Their Anticancer Activity - Mahmood Shakir Magtoof (Journal of Global Pharma Technology, 2018)
We describe the syntheses of 3,4-Dihydropyrimidine-2(1H)Ones/Thiones by a one-pot cyclocondensation of urea or thiourea, aldehydes and ethylacetoacetates using Ferric (III) Chloride as catalyst, this method has the advantage of excellent yields (55–93%) and short reaction time (6-7 hours). Furthermore, we have studied the antioxidant activities of these synthesized 3,4-Dihydropyrimidine-2(1H)Ones/Thiones. Some the synthesized compounds appear the Important antioxidant properties, these properties studied by using 1,1-diphenyl-2-picrylhydrazyl (DPPH) free radical scavenging assays. The cellular toxicity of the compound 1 was studied on (MCF7) cell lines using MTT assay that revealed the presence of a toxic effect of the cells with the highest activity of the compound 1 on (MCF7) cell lines. This indicates that compound 1 has an antioxidant and anticancer effect and can be used as a new chemical compound but this needs further investigation in vivo to confirm our results in vitro. The compounds were established on the basis of the spectral studies using IR,1H-NMR, 13C-NMR, and Mass spectra.Key words: Aldehydes, urea/thiourea, Ethyl acetoacetates, Anticancer, Antioxidant, MCF7.